2013
DOI: 10.1177/2047487313501278
|View full text |Cite
|
Sign up to set email alerts
|

Geographic differences in outcomes in outpatients with established atherothrombotic disease: results from the REACH Registry

Abstract: There are important variations in the outcomes of patients with atherothrombotic across geographic regions. These observations have important implications for public health and clinical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
0
16
0
3
Order By: Relevance
“…Asian populations have consistently been shown to be at a higher overall risk of stroke than white populations. [27][28][29] The REACH registry 30,31 showed that, although Eastern Europe was the region in which patients were at highest risk of composite cardio vascular and cerebrovascular outcomes, individuals in Japan had the highest risk of haemorrhagic stroke. The relative burden of stroke compared with ischaemic heart disease is significantly greater in Asian countries, particularly China, compared with the West, as is the cost in d isability-adjusted life years.…”
Section: Af and Stroke Epidemiology In Asiansmentioning
confidence: 99%
“…Asian populations have consistently been shown to be at a higher overall risk of stroke than white populations. [27][28][29] The REACH registry 30,31 showed that, although Eastern Europe was the region in which patients were at highest risk of composite cardio vascular and cerebrovascular outcomes, individuals in Japan had the highest risk of haemorrhagic stroke. The relative burden of stroke compared with ischaemic heart disease is significantly greater in Asian countries, particularly China, compared with the West, as is the cost in d isability-adjusted life years.…”
Section: Af and Stroke Epidemiology In Asiansmentioning
confidence: 99%
“…Residual ischemic risk was uniformly distributed over the different geographic areas, except for Japan, where patients experienced lower event rates. The explanations for such differences have been described previously . Briefly, differences in disease management and medication use have been reported (in particular, the use of clopidogrel is substantially higher in Japan than in other regions of the world), which may have contributed to some extent in the improved outcomes in Japan, supported by evidence that clopidogrel use may be superior to aspirin in reducing major CV events in PAD patients .…”
Section: Discussionmentioning
confidence: 88%
“…In addition, gaps in country‐based payer policies and healthcare systems might explain differences in risk factor prevalence and management. Moreover, genetic susceptibilities and lifestyle differences may also play a role in risk variation . Nevertheless, residual risk remains high, and events accrued progressively over time across all geographic areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As event rates vary between geographic areas,27, 28 recalibration to the population of interest is often necessary. This resulted in accurate estimates of the REACH‐SMART model in the external validation sets.…”
Section: Discussionmentioning
confidence: 99%